ENSURING ELDERLY RIGHTS: EXPLORING LIFETIME SUPPORT CONTRACTS IN EU MEMBER STATES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
The Article 25 of the Chapter of Fundamental Rights of the EU recognizes the rights and protection of elderly people, this paper aims to elaborate on whether a lifetime support contract can be used as a legal instrument to ensure effective enforcement of Article 25.In the first part, this paper will analyze the possible participants/parties in the lifetime maintenance agreement vis-a-vis the subject/s who are responsible for ensuring the effective protection of the rights of the elderly. In particular, the article will analyze who can be a subject of the contract vis-à-vis, who is responsible for ensuring the effective enjoyment of the rights, and protection of elderly people under EU Law. In the second part of the paper, we will analyze the second problem related to the need to improve the legal protection of the elderly who are involved in these agreements. The lack of legal knowledge among these people often results in an incorrect understanding of their rights and obligations, which can lead to unforeseen consequences when it comes to support and property issues. In many cases, the elderly may not be aware that they are entitled to legal aid or cannot afford to wait for court decisions due to their age. Finally, the third part of the paper will deal with the regulation of the lifetime support agreement in the EU member states and how it is regulated in the legal systems.This paper will give an analysis of legal texts, court decisions, and how theoretical positions are carried out, to see which subjects appear in this type of contract and what their rights and obligations are. The comparative method will be applied to investigate the regulation of this agreement in the EU member states and to determine whether it is regulated consistently. The main goal is to identify the differences and similarities between different legal systems and their protection of the rights of the elderly. This paper will also propose recommendations for improving the arrangement of this legal institute.
Keywords: Lifetime support contracts, elderly rights, Article 25 CFREU, legal protection, EU member states, comparative analysis, legal regulation